Strategies To Increase Financial Access For Small Medium Enterprises Case Study: Trisakti Vegetable Trading Business - Elrisa Marsanda Br Ginting; Juli Kristabel Sinaga; Leonardo Siahaan; Lola Br Ginting; Lola Vitaloka Simanjuntak (CV Pena Jaya Pers, 2025)
MSMEs have a strategic role in supporting Indonesia's economic growth, but often face major challenges, including limited access to capital. This study aims to analyze capital challenges and formulate strategies to improve access to capital for UD Sayur Trisakti, an MSMEs operating in the agribusiness sector. Using a qualitative descriptive approach and SWOT analysis, this study found that limited capital, fluctuations in raw material prices, and dependence on local suppliers are the main obstacles. As a solution, it is recommended to utilize financing programs such as People's Business Credit (KUR), financial literacy training, and the use of digital technology such as crowdfunding. The results of this study are expected to be a practical reference for other MSMEs and for policy makers in designing more effective support for the MSMEs sector. Keywords: MSMEs, access to capital, SWOT analysis, development strategy.